Speaking on climate : a guide to speechwriting for a better future - Kier Nielsen, Rune (Zest Books, 2025)
"What makes a speech well written, memorable, and effective? And how can someone apply those skills to climate justice? Former UN Public Advocacy Lead on Climate Action and award-winning speechwriter Rune Kier Nielsen will answer these questions and more in this timely guide"-- Provided by publisher.